Proses Inovasi Pendidikan: Keputusan, Difusi, dan Diseminasi - Azzahra, Radhita; Ismail, Fajri; Afgani, Muhammad Win (Jurnal Ilmiah Wahana Pendidikan, 2025)
Innovation in education is closely related to continuous change, aiming to enhance learning effectiveness and achieve educational goals. Particularly in Islamic education, the focus is on improving learning innovations to help students master subjects efficiently. In the era of globalization, educational innovation plays a crucial role in shaping effective teaching and learning processes. This study explores the process of educational innovation through three key stages: decision-making, diffusion, and dissemination. Decision-making involves evaluating and accepting or rejecting new educational approaches. Diffusion refers to the communication process in spreading innovative ideas, while dissemination ensures the systematic distribution of innovations for broader implementation. This research employs a library research method, analyzing relevant theories from academic sources such as journals, books, and previous studies. The findings highlight that successful educational innovation depends on well-structured decision-making, effective diffusion strategies, and comprehensive dissemination processes. Additionally, teachers play a vital role in implementing educational innovation, as their involvement significantly impacts the success of new learning methods. Innovation in education must align with Indonesia's educational needs, incorporating curriculum development, teaching methodologies, and technological integration. The structured adoption of innovation ensures that education remains relevant, efficient, and adaptable to changing times